CFD Contribution forthe Investigation ofa UAV Aerodynamic Performances Using the Spalart-Allmaras Turbulence Model - Z. Imine; M. Senouci; T. Yahiaoui; S.M.A. Meftah (Algerian Journal of Research and Technology (AJRT), 2021)
In this paper, a numerical simulation of a turbulent flow around a UAV is performed. Different angles of incidence were used to evaluate aerodynamic performance. The Navier-Stocks equations are closed using a Spalart-Allmaras turbulence model. The results of the current numerical investigation were in good agreement with those found in the literature.Variations in lift and drag allow us to determine the total take-off weight and effective power required to move this UAV in various flight configurations (take-off, cruise flight, and landing). The contours of the total pressure around the UAV have been determined to have a preliminary observation on the parts of the UAV most in demand by the dynamic pressures.